2013
DOI: 10.1093/bioinformatics/btt173
|View full text |Cite
|
Sign up to set email alerts
|

KGVDB: a population-based genomic map of CNVs tagged by SNPs in Koreans

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In recent years, each of genotyping arrays, array-CGH microarrays, and next-generation sequencing have all been implemented successfully to detect structural variation in human cohorts (reviewed in [ 45 ]). While the majority of studies continue with HapMap cohorts, there has been a recent increase in the number of reports from non-HapMap populations, the majority of which are still ancestrally similar to pre-existing HapMap populations (e.g., East Asian populations) [ 51 53 ]. To date, however, there has been no systematic characterization of CNVs in Gulf Arabs, a population witnessing a growth in clinical genomics testing but whose ancestry is not adequately represented in current HapMap and 1000 Genomes populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, each of genotyping arrays, array-CGH microarrays, and next-generation sequencing have all been implemented successfully to detect structural variation in human cohorts (reviewed in [ 45 ]). While the majority of studies continue with HapMap cohorts, there has been a recent increase in the number of reports from non-HapMap populations, the majority of which are still ancestrally similar to pre-existing HapMap populations (e.g., East Asian populations) [ 51 53 ]. To date, however, there has been no systematic characterization of CNVs in Gulf Arabs, a population witnessing a growth in clinical genomics testing but whose ancestry is not adequately represented in current HapMap and 1000 Genomes populations.…”
Section: Discussionmentioning
confidence: 99%
“…As detection methods continue to improve, so will the discovery of new genes and loci whose deletion or duplication could lead to morbid clinical phenotypes in specific populations. This kind of population specificity will have detrimental effects on the design of population-specific clinical CHG-arrays, and on the interpretation and assignment of pathogenicity of CNV findings in individuals from different ethnic populations [ 25 , 51 54 ]. This issue is of special relevance to Arabs in general and Qataris specifically, for whom there is a paucity of databases of CNVs observed in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…We first used the 3,601 CNVRs from the previous Korean CNV study using 4,694 individuals 20 . These were part of 8,842 Korea Association Resource (KARE) Project genome-wide association study (GWAS) subjects who satisfied quality control criteria, including exclusion of any kind of cancer samples (n = 101) from 10,038 subjects (Figure S1A) 21 …”
Section: Methodsmentioning
confidence: 99%
“…To investigate CNV-miRNAs in the Korean population, CNV regions from our previously reported CNV study were analyzed (22). Briefly, 4,694 samples that are part of the Korean Genome Epidemiology Study were genotyped with the NimbleGen HD2 3x720 K comparative genomic hybridization array.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, our previously reported CNV data that were obtained from population-based genome-wide approaches (22) was analyzed and candidate CNV-miRNAs with biological functions were identified. Additionally, the roles of miR-650 in the production of IL6, which is induced by IL1B in human MG-63 osteosarcoma cells, were investigated.…”
Section: Introductionmentioning
confidence: 99%